Yersinia pseudotuberculosis Infection Complicated with Bacteremia in a 10-Month-Old Boy - Takuro Kamura; Yuhei Tanaka; Naoya Tsumura; Takashi Ohya; Yuki Okamatsu (Hindawi Limited, 2020)
Yersinia pseudotuberculosis (Y. pseudotuberculosis) infection complicated with bacteremia rarely occurs. Y. pseudotuberculosis infection is also known to produce various symptoms similar to Kawasaki disease (KD) due to the production of Y. pseudotuberculosis-derived mitogen (YPM), an exotoxin with superantigen activity. Moreover, it causes terminal ileitis and is responsible for appendix swelling. Here, we report a case of Y. pseudotuberculosis infection in a 10-month-old boy who was brought to our hospital due to fever, watery stool, and poor vitality. Abdominal echocardiography revealed wall thickening of the entire colon and appendix swelling; therefore, he was admitted and treated with antibiotics for bacterial enteritis or appendicitis. After the antibiotic administration, facial skin rashes and hand and foot edema developed. However, he had 5/6 major symptoms of KD and was diagnosed with Y. pseudotuberculosis infection because of its presence in the blood and stool cultures. Thereafter, antibacterial therapy improved his symptoms and increased the inflammatory response. After his hospital discharge, the skin on his fingers showed desquamation like that of KD. Y. pseudotuberculosis infection should be considered as a differential disease in KD, terminal ileitis, and appendicitis. Furthermore, its infection route and culture methods should also be carefully considered.